2017
DOI: 10.1002/ecs2.1956
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear effects of temperature and precipitation on ecosystem properties in tidal saline wetlands

Abstract: . 2017. Linear and nonlinear effects of temperature and precipitation on ecosystem properties in tidal saline wetlands. Ecosphere 8(10):e01956. 10. 1002/ecs2.1956 Abstract. Climate greatly influences the structure and functioning of tidal saline wetland ecosystems.However, there is a need to better quantify the effects of climatic drivers on ecosystem properties, particularly near climate-sensitive ecological transition zones. Here, we used climate-and literature-derived ecological data from tidal saline we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 168 publications
(219 reference statements)
4
73
0
1
Order By: Relevance
“…Mangroves responded strongly to warming according to most of the growth parameters measured, including a doubling of height and canopy volume, which contributed to an increase in mangrove dominance. This is consistent with predictions by Feher et al () where increases in the minimum temperature were associated with increased canopy height of coastal wetland species. However, we previously found that mangrove seedlings had minimal response to chronic warming, this study shows that once mangroves are established, their growth rate is enhanced in warmed conditions, which may help drive salt marsh habitat conversion to mangrove habitat (Coldren et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mangroves responded strongly to warming according to most of the growth parameters measured, including a doubling of height and canopy volume, which contributed to an increase in mangrove dominance. This is consistent with predictions by Feher et al () where increases in the minimum temperature were associated with increased canopy height of coastal wetland species. However, we previously found that mangrove seedlings had minimal response to chronic warming, this study shows that once mangroves are established, their growth rate is enhanced in warmed conditions, which may help drive salt marsh habitat conversion to mangrove habitat (Coldren et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Mangrove encroachment into salt marsh habitats can alter below‐ground C storage, due to increased root production (Kelleway et al, ; Yando et al, ). However, effects are not consistent across locations and above‐ and below‐ground biomass capacity of C storage can differ (Feher et al, ; McKee & Vervaeke, ; Perry & Mendelssohn, ; Yando et al, ). Both salt marshes and mangroves can exhibit high levels of root production and sediment trapping, processes that can maintain biome position with respect to sea levels (Langley, McKee, Cahoon, Cherry, & Megonigal, ; McKee, Cahoon, & Feller, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are three common mangrove species in this region: A. germinans (black mangrove – the focal species for this study), Rhizophora mangle (red mangrove) and Laguncularia racemosa (white mangrove). Near these northern range limits, winter air temperature extremes greatly influence mangrove physiology (Cook‐Patton, Lehmann, & Parker, ; Hayes et al, ; Madrid, Armitage, & López‐Portillo, ; Stuart et al, ), reproduction (Dangremond & Feller, ) and architecture (Doughty et al, ; Feher et al, ; Simpson, Osborne, Duckett, & Feller, ; Yando et al, ). Freeze‐tolerant salt marshes dominate areas that are too cold for mangrove forests, while mangroves dominate coastal reaches with mild winters.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have looked at combined effects of sea level rise and other aspects of climate change. Feher et al (2017) reviewed the literature on the influence of changing temperature and precipitation regimes on tidal saline wetlands. They found that for several ecosystem properties and many regions there was still insufficient evidence to make generalized predictions.…”
Section: Salt Marsh and Mangrove Response To A Changing Climate And Amentioning
confidence: 99%